2019
DOI: 10.31635/ccschem.019.20190030
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Cross-Linked Protein-Imprinted Polymers: Easy Template Removal and Excellent Imprinting Effect

Abstract: Molecular imprinting of proteins remains a huge challenge because of two major obstacles: difficulty in template removal and low imprinting efficiency. Herein, we propose a new strategy to simultaneously overcome these two challenges by creating molecularly imprinted polymers (MIPs) with nanoscale shape-memorable imprint cavities. These novel MIPs were developed by simply cross-linking the polymers with a peptide cross-linker instead of commonly used cross-linkers. Due to the unique pH-induced helixcoil transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Shape memory polymers (SMPs) are smart materials that can fix temporary shapes under certain conditions and recover their permanent shapes upon external stimulus, such as light, heat, pH, and moisture. Overall, SMPs are generally composed of reversible phase to fix the temporary shape and the stable cross-linked network to keep the permanent shape. , This unique property of SMPs imparts them with tremendous promising applications in various advanced engineering fields, including deployable aerospace structures, biomedical devices, soft robotics, and electronic instruments. …”
mentioning
confidence: 99%
“…Shape memory polymers (SMPs) are smart materials that can fix temporary shapes under certain conditions and recover their permanent shapes upon external stimulus, such as light, heat, pH, and moisture. Overall, SMPs are generally composed of reversible phase to fix the temporary shape and the stable cross-linked network to keep the permanent shape. , This unique property of SMPs imparts them with tremendous promising applications in various advanced engineering fields, including deployable aerospace structures, biomedical devices, soft robotics, and electronic instruments. …”
mentioning
confidence: 99%
“…In general, molecular imprinting involves polymerization that occurs in the presence of a template, which is bound covalently or non-covalently to the polymer scaffold (BelBruno, 2019). Removal of the template after polymerization results in a structure with sites that are tailored to bind an analyte which is similar to the template (Xu et al, 2019b). MIPs have found success in a variety of applications, including in chromatography (Bereli et al, 2020), sensing (Wang et al, 2020d), and catalysis (Muratsugu et al, 2020).…”
Section: Fluorescent Polymer-based Pesticide Detectionmentioning
confidence: 99%
“…It was found that the polymer binding capacity was significantly higher at 28°C compared to 44°C because the polymer presents a hydrophilic and swelling state at 28°C, which enables easy access of the target molecules to the imprinted cavities [46]. Nonetheless, polymer chains prepared with NIPAm fold randomly during transition from extended coil structure to a collapsed globule structure, therefore the conformation of the newly formed globules might differ from the original one, which in turn can affect the structural selectivity of the polymer [47]. Some researchers reported synthesis of monomers that have a specific functionality to be used in MIPs.…”
Section: A) Functional Monomermentioning
confidence: 99%
“…Cross linkers may also be synthesised according to the required functional needs. R. Xu et al [47] reported the synthesis of a new peptide cross linker that exhibited a pH dependent helix-coil transition properties. Therefore, changing the pH from 5.5 to 7.4 led to expansion of the imprinted cavities and easy template removal; restoring the pH to 5.5 returned the imprinted cavities to their original shape and size due to the precise peptide folding.…”
Section: B) Cross Linkermentioning
confidence: 99%